Molecular detection of Leishmania infantum, filariae and Wolbachia spp. in dogs from southern Portugal - Maia, Carla (2018)
BACKGROUND: Leishmaniosis caused by the protozoan Leishmania infantum and dirofilariosis caused by the nematodes Dirofilaria immitis or Dirofilaria repens are vector-borne zoonoses widely present in the Mediterranean basin. In addition, some studies reported that the endosymbiont Wolbachia spp. play a role in the biology and pathogenesis of filarial parasites. The aim of this work was to evaluate the frequency of mono- and co-infections by L. infantum, filariae and Wolbachia spp. and their association with clinical signs in dogs from the south of Portugal. Leishmanial, filarial and Wolbachia spp. DNA were evaluated by specific real-time polymerase chain reaction (qPCR) assays in blood samples from 230 dogs. FINDINGS: One hundred and thirty-nine (60.4 %) dogs were qPCR-positive for L. infantum and 26 (11.3 %) for filariae (24 for D. immitis only, one D. immitis and for Acanthocheilonema dracunculoides and another one for Acanthocheilonema reconditum only). Wolbachia spp. DNA was amplified from 16 (64.0 %) out of the 25 D. immitis-positive dogs. Nineteen (8.3 %) dogs were co-infected with L. infantum and D. immitis, including the one (0.4 %) A. drancunculoides-positive animal. In dogs without clinical signs consistent with leishmaniosis and/or dirofilariosis, L. infantum prevalence was 69 %, whereas in those dogs with at least one clinical manifestation compatible with any of the two parasitoses prevalence was 42.7 %. Leishmania prevalence was significantly higher in apparently healthy mongrels (77.2 %) and pets (76.9 %) than in defined-breed dogs (including crosses; 58.8 %) and in dogs with an aptitude other than pet (i.e. farm, guard, hunting, shepherd or stray), respectively, whereas in those dogs with at least one clinical sign, the detection of L. infantum DNA was higher in males (53.3 %) and in those dogs not receiving insect repellents (52.8 %). CONCLUSIONS: The molecular detection of canine vector-borne disease (CVBD) agents, some of which are zoonotic, reinforces the need to implement efficient prophylactic measures, such as insect repellents and macrocyclic lactones (including compliance to administration), in the geographical areas where these agents are distributed, with the view to prevent infection and disease among mammalian hosts including humans.